The Emergence of Education 4.0 Trends in Teaching Arabic Islamic Finance Curriculum Design: A Case Study - Anas Al Muhsin, Muhammad; Ahmad, NorZahidah (International Journal of Psychosocial Rehabilitation, 2019)
Purpose of the study: The paper explores the characteristics of curriculum in designing Arabic for Islamic Finance module, the motivations in learning Arabic, and the importance of need analysis in designing a module for learning Arabic for specific purposes. Methodology: In this study we conducted interviews with a group of undergraduate students, majoring in Islamic finance at Sultan Ahmad Shah Pahang Islamic University College (KUIPSAS). We also interviewed an experienced lecturer who has been teaching Arabic for Islamic finance courses, to give an overview for the elements needed in designing a course module that fulfilling Education 4.0 trends. [Done] Main Findings: The findings highlighted that the need for concrete activities and selected learning strategies in teaching and learning Arabic for Islamic finance as suggested by respondents, such as discussion, and task-based learning. [Done] Applications of this study: The needs analysis revealed the basic features, approaches, activities, and language skills that should be applied in lessons, thus giving the developer and lecturer ideas for designing a resourceful module for this course. At the same time, we are able to find out students’ lacks and needs when studying Arabic for their future professional careers. [Done] Novelty/Originality of this study: Greater focus given on communicative skills, and writing skills based on learner-centered approaches and real-life situations supported by using authentic materials that are efficient for the students’ engagement into the real-life industry. [Done]